The CNC Handbook : Digital Manufacturing and Automation from CNC to Industry 4.0. - Kief, Hans Bernhard (Industrial Press, Inc., 2022)
Comparison Tables CNC/PLC -- Important Points to Remember -- Effects of CNC on Machine Components -- Machine Configuration -- Machine Frames -- Guides -- Machine Enclosures -- Coolant Supply -- Chip Removal -- Summary -- Important Points to Remember -- PART 3 -- Electrical Drives of CNC Machine Tools -- Drive Control for CNC Machine Tools -- Definition -- Mechanical Axis -- Analog Control -- Analog versus Digital Position Control -- Digital Intelligent Drive Technology -- Controller Types and Controlling Behavior -- Loop Gain and Kv Factor -- Precontrol -- Frequency Converter.